2017
DOI: 10.1074/jbc.m117.793497
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for generating bispecific antibodies based on a common light chain format and the stable architecture of human immunoglobulin G1

Abstract: Edited by Peter CresswellBispecific antibodies combine two different antigen-binding sites in a single molecule, enabling more specific targeting, novel mechanisms of action, and higher clinical efficacies. Although they have the potential to outperform conventional monoclonal antibodies, many bispecific antibodies have issues regarding production, stability, and pharmacokinetic properties. Here, we describe a new approach for generating bispecific antibodies using a common light chain format and exploiting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 30 publications
(25 reference statements)
0
71
0
Order By: Relevance
“…However, applying bsAbs requires maintaining the natural antibody structure and the ability for large-scale production of high-quality material, which has proven challenging with these engineered sequences. A study by De Nardis et al (3) now demonstrates one solution to this problem, facilitated by pairing oppositely charged amino acids across the heterodimer interface.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, applying bsAbs requires maintaining the natural antibody structure and the ability for large-scale production of high-quality material, which has proven challenging with these engineered sequences. A study by De Nardis et al (3) now demonstrates one solution to this problem, facilitated by pairing oppositely charged amino acids across the heterodimer interface.…”
mentioning
confidence: 99%
“…These unexpected backbone rearrangements and novel interactions may account for the favorable stability of the molecule, making it a very attractive platform for the development of novel bsAbs. De Nardis et al (3) further demonstrated the utility of the DEKK design to construct a highly stable bsAb targeting HER2 and HER3 and to produce it using known protocols and, under GMP conditions, providing proof-of-concept that the DEKK design can yield bsAbs that can be used in the clinic.…”
mentioning
confidence: 99%
See 3 more Smart Citations